Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù„ØºÙˆÙŠ: ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¬ØªÙ…Ø¹ Ù…ØªØ¹Ø¯Ø¯ Ø§Ù„Ù„ØºØ§Øª Ø¨Ù…Ø¹Ù‡Ø¯ "Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ù„Ù„Ø¨Ù†Ø§Øª" Ù„Ø§Ù…Ø¨ÙˆÙ†Ø¬ - Basyori, Ahmad (Asalibuna, 2019)
This research aims to discover and analyze related aspects of teaching Arabic as follows: (1) the planning of teaching Arabic, (2) material that is used in the Arabic language teaching, (3) the steps of teaching Arabic, (4) the impact of multilingualism against linguistic activity in the boarding school. This research used the qualitative approach with descriptive analytical method. The results showed that: (1) The planning of teaching Arabic at the lodge include the planning of the boarding school as a whole by recruiting and assigning teachers with teaching Arabic competence, while planning of the teacher executed through a learning device; (2) Material that is used in the Arabic language teaching taken from a variety of different types of books; (3) The steps of Arabic language teaching are point to eclectic method using, with the help of code-switching and mixing from the Arabic language to the English or Bahasa; (4) The impact of multilingualism from language society at this Boarding School Lampung is the Arabic language teaching use the code-switching and mixing. And the multilingualism of multilingual society impact to many kinds of language activities, which is the Arabic language become the main language for using in this boarding school.